Examining cooperation with the police in a national security environment. Issue 2 (2nd July 2016) - Williamson, Harley
ABSTRACT: Threats of terrorism on a national and global level have catalysed the introduction of a series of national security measures within Australia. The nature of these measures has put pressure on the role of police and the willingness of citizens to cooperate with police in their regular duties. This study uses the National Security and Preparedness Survey to examine the extent to which the perceived effectiveness of such measures influences individual perceptions of procedural justice of the police and people's willingness to cooperate with law enforcement. Particular attention is paid to the role of procedural justice in influencing perceptions of police in the national security context. The findings highlight the factors that are important for enhancing positive attitudes towards law enforcement agencies in a post 9/11 environment driven by national security threats.